Multidirectional sprints in soccer: are there connections between linear, curved, and change-of-direction speed performances? - Freitas, T. T.; Jeffreys, I.; Reis, V. P.; Fernandes, V.; Alcaraz, P. E.; Pereira, L. A.; Loturco, I. (The Journal of Sports Medicine and Physical Fitness, 2021)
BACKGROUND: The aim of this study was to investigate the relationships between linear sprint, curve sprint (CS) and change of direction (COD) abilities and vertical jump performance in elite young soccer players. METHODS: Twenty-nine players from the same soccer club participated in this study. On the same day, athletes performed countermovement jump (CMJ), 17-m linear sprint (with a 10-m split time), CS (for both sides) and COD tests. A Pearson product moment correlation was performed to determine the associations between the assessed variables. Significance level was set at P<0.05. RESULTS: Linear sprint was significantly related to CS (r ranging from 0.67 and 0.76; P<0.05) but not to COD performance (r=0.23 and 0.33 for 10- and 17-m, respectively; P>0.05). CS ability (for both good and weak sides) was significantly associated with COD performance (r=0.60 and 0.54, respectively; P<0.05). CMJ height was significantly correlated with both linear and CS velocities (r varying between 0.50 and 0.68; P<0.05), but not with COD velocity (r=0.37; P>0.05). CONCLUSIONS: Based on these findings, it is possible to suggest that training strategies designed to improve vertical jumping capacity may potentially improve both linear and curvilinear sprint abilities. Moreover, increases in COD velocity may also produce positive changes in CS performance.